Teacher educators for new times? Redefining an important occupational group. Issue 2 (15th March 2019) - White, Simone
ABSTRACT: Teacher educators are an occupational group currently experiencing increased scrutiny by international policy makers and researchers alike. This occupational group however is increasingly difficult to define and identify in a complex, internationally changing teacher education policy reform environment. The question posed is an enduring one: who is a teacher educator? The answer is more complicated. To better understand this occupational group, a literature review and local policy analysis study using the Australian context was conducted to reveal more about their identity; career trajectories and; professional learning needs. Analysis revealed that three sub-groups belonging to the broader teacher educator occupational group have emerged as a result of shifting teacher education policies. Namely, university-based; school-based and community-based teacher educators, each with an important role to play and each positioned differently within the research and policy landscape. Findings suggest that all three groups are important to educating teachers across their career and to best meet the needs of all students for new times. Recommendations are made for future research and practice into how these groups can work collectively together, within and across the multiple sites of learning to teach.